C-C motif chemokine receptor 6-mediated pro-inflammatory mediator expression is associated with immune dysfunction in children with autism. (March 2020) - Ansari, Mushtaq A.; Bakheet, Saleh A.; Al-Ayadhi, Laila Y.; Khan, Mohammad R.; Attia, Sabry M.; Ahmad, Sheikh F.
Highlights: CCR6 + cells were abundant in children with ASD. CCR6 mRNA and protein expression was induced in children with ASD. Inflammatory mediator production was increased in CCR6 + cells in children with ASD. CCR6 expression could be critical for neuroimmune dysfunction in patients with ASD. Abstract: Autism spectrum disorder (ASD) is a heterogeneous disorder associated with immune abnormalities. C-C motif chemokine receptor 6 (CCR6) has central roles in neuroinflammatory disorders. However, CCR6 expression in ASD is unclear. Here, we examined CCR6 expression in children with ASD. Children with ASD had significantly increased numbers of CCR6 + /interferon-γ +, CCR6 + /tumor necrosis factor-α +, CCR6 + /interleukin (IL)-9 +, CCR6 + /IL-22 +, CCR6 + /nuclear factor-κB p65 +, and CCR6 + /nitric oxide synthase 2 + cells compared with typically developing controls (TDs). Moreover, children with ASD showed increased CCR6 mRNA/protein levels compared with TDs. Thus, CCR6 upregulated pro-inflammatory mediators associated with immune dysfunction in children with ASD, suggesting contributions to ASD development.